2011
DOI: 10.1104/pp.111.173427
|View full text |Cite
|
Sign up to set email alerts
|

Rice ABI5-Like1 Regulates Abscisic Acid and Auxin Responses by Affecting the Expression of ABRE-Containing Genes    

Abstract: Abscisic acid (ABA) regulates plant development and is crucial for plant responses to biotic and abiotic stresses. Studies have identified the key components of ABA signaling in Arabidopsis (Arabidopsis thaliana), some of which regulate ABA responses by the transcriptional regulation of downstream genes. Here, we report the functional identification of rice (Oryza sativa) ABI5-Like1 (ABL1), which is a basic region/leucine zipper motif transcription factor. ABL1 is expressed in various tissues and is induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 54 publications
(68 reference statements)
3
100
0
Order By: Relevance
“…Based on the observation that OsPM19L1 was dramatically induced by ABA treatment, it may play an important role in ABA signaling. The ABL1 protein is localized to the nucleus and modulates the plant stress and ABA responses by directly regulating the ABRE-containing genes (Yang et al, 2011). An ABRE protein binding site in the promoter region of OsPM19L1 suggests that OsPM19L1 may participate in plant stress and ABA responses under the regulation of ABL1 transcription factor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the observation that OsPM19L1 was dramatically induced by ABA treatment, it may play an important role in ABA signaling. The ABL1 protein is localized to the nucleus and modulates the plant stress and ABA responses by directly regulating the ABRE-containing genes (Yang et al, 2011). An ABRE protein binding site in the promoter region of OsPM19L1 suggests that OsPM19L1 may participate in plant stress and ABA responses under the regulation of ABL1 transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…The rice (Oryza sativa L. ssp japonica) cultivars Jiucaiqing, Zhonghua11 (ZH11), and abl1 mutant of Zhonghua11 (Yang et al, 2011) were used in this study. The seeds were sterilized in 0.1% HgCl 2 and germinated at 30°C.…”
Section: Plant Materials and Stress Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yang et al (2011) have shown that rice ABI5-Like1 (ABL1) regulates ABA and auxin responses through ABRe-containing wRKY genes. OsWRKY69 has an ABRe element in its promoter that leads to specific binding of the bZIP transcription factor (ABL1), which suppresses auxin signaling while enhancing ABA signaling and hence provides insights into ABA and auxin crosstalk ).…”
Section: Transcription Factors and Droughtmentioning
confidence: 99%